2020
DOI: 10.3389/fnbeh.2020.00159
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary Dilations of Mice Performing a Vibrotactile Discrimination Task Reflect Task Engagement and Response Confidence

Abstract: This confidence coding is overlaid within a more pronounced pupil dilation that reflects post-decision components that are related to the response itself but not to the decision. We also provide evidence as to how different behavioral states, imposed by task demands, modulate what the pupil is reflecting, presumably showing what the underlying cognitive network is coding for.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 62 publications
8
31
0
Order By: Relevance
“…Each paper was indexed in an average of 3.11 of the included databases (SD = 1.45). Science Citation Index Expanded from Web of Science was the database with more papers indexed in; the only paper that was not indexed by them was the one from Ganea et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each paper was indexed in an average of 3.11 of the included databases (SD = 1.45). Science Citation Index Expanded from Web of Science was the database with more papers indexed in; the only paper that was not indexed by them was the one from Ganea et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…As Table 2 and Figure 3 show, the nine studies were conducted between 1996 and 2020. Three used human subjects (two with adults and one with adolescents) (Van Hooijdonk et al, 2019 ; Bertheaux et al, 2020 ; Mückschel et al, 2020 ), one wild mice (Lee and Margolis, 2016 ), two with C57BL6J mice (Ganea et al, 2020 ; Lee et al, 2020 ), two albino rats (Schriver et al, 2018 , 2020 ), and one juvenile male Japanese monkeys ( Macaca fuscata ) (Iriki et al, 1996 ). Four studies used go/no-go tasks (Lee and Margolis, 2016 ; Schriver et al, 2018 , 2020 ; Mückschel et al, 2020 ), one a vibration detection task (Lee et al, 2020 ), one a two-alternative forced choice (2AFC) task (Ganea et al, 2020 ), one used a passive task (Iriki et al, 1996 ), and two discrimination of affective touch tasks (Van Hooijdonk et al, 2019 ; Bertheaux et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Locomotion and pupil diameter can be considered behavioral indications of engagement with the environment (Jacobs et al, 2018; Ganea et al, 2018; Bennett et al, 2013) and modulate neuronal activity in visual cortex (Dadarlat & Stryker, 2017; McGinley, David, et al, 2015; McGinley, Vinck, et al, 2015; Niell & Stryker, 2010; Polack et al, 2013; Reimer et al, 2014; Salkoff et al, 2020; Vinck et al, 2015). We found that in L2/3 of AL & AM, effect sizes were positively correlated with locomotion activity ( Figure 4 , top left; Pearson’s r = 0.896; two-sided t -test; t (4) = 4.030, p = 0.0157) and pupil diameter ( Figure 4 , top right; r = 0.716; t (42) = 2.054, p = 0.109), suggesting that the difference in ND is more clear when the animal is engaged with the stimuli.…”
Section: Resultsmentioning
confidence: 99%